(untitled) (Journal of Imam Al-Kadhim College, 2024)
This study aims to track the interactions of Algerian-Iranian relations, and focus on their economic dimensions in order to strengthen their economic position in the world, especially since economic and strategic diplomacy remains one of the appropriate approaches to stabilizing those relations between the two countries in particular Its future impact of international plans within major international trends to revive their economies and achieve their national interests within the framework of fruitful relations that allow the two countries to defend their national interests.